The influence of nanoporous anodic aluminum oxide on the initial adhesion of Streptococcus mitis and mutans - Taxis, Jürgen; von Wilmowsky, Cornelius; Pedimonte, Birgit; Beuscher, Horst-Ulrich; Ries, Jutta; Kesting, Marco Rainer; Möst, Tobias (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2019)
The use of nanoscale surface modifications offers a possibility to regulate the bacterial adherence behavior. The aim of this study was to evaluate the influence of nanoporous anodic aluminum oxide of different pore diameters on the bacterial species Streptococcus mitis and Streptococcus mutans. Nanoporous anodic aluminum oxide (AAO) surfaces with an average pore diameter of 15 and 40 nm, polished pure titanium and compact aluminum oxide (alumina) samples as reference material were investigated. S. mitis and mutans were evaluated for initial adhesion and viability after an incubation period of 30 and 120 min. After 30 min a significantly reduced growth of S. mitis and mutans on 15 nm samples compared to specimens with 40 nm pore diameter, alumina and titanium surfaces could be observed (p <.001). Even after 120 min incubation there was a significant difference between the surfaces with 15 nm pore diameter and the remaining samples (p <.001). AAO surfaces with a small pore diameter have an inhibitory effect on the initial adhesion of S. mitis and mutans. The use of such pore dimensions in the area of the implant shoulder represents a possibility to reduce the adhesion behavior of these bacterial species.
CRIS-Team Scopus Importer:2019-12-03
Keywords: biofilm; initial adhesion; nanoporous anodic aluminum oxide; Streptococcus mitis; Streptococcus mutans